Comparison of SDOCT Scan Types for Grading Disorganization of Retinal Inner Layers and Other Morphologic Features of Diabetic Macular Edema - Sampani, Konstantina (Transl Vis Sci Technol, 2020)
PURPOSE: To assess grading reproducibility of disorganization of the retinal inner layers (DRIL) and other morphologic features of diabetic macular edema (DME) across spectral domain optical coherence tomography (SDOCT) instruments and scan types. METHODS: A cross-sectional study enrolled participants with current or recent center-involved DME. In group A (27 eyes), we obtained two Cirrus scans (512 × 128 macular cube [Cube] and high-definition five-line raster [HD 5-Line]) and two Spectralis scans (high-resolution [HR] and high-speed [HS]). In group B, 26 eyes underwent HR scans and Optovue AngioVue (OP) 3 × 3-mm scans. All scans were graded for type and extent of DRIL, intraretinal cysts, cone outer segment tip visibility, and subretinal fluid (SRF). RESULTS: In the total cohort, mean central subfield thickness was 342.9 ± 83.4 µm. Intraclass correlations were high for DRIL extent across the four different imaging settings (HR vs. HS, r = 0.93; HR vs. Cube, r = 0.84, HR vs. HD 5-Line, r = 0.76, HR vs. OP, r = 0.87) and ranged from good to excellent for intraretinal cyst and SRF area. There were significantly smaller mean normalized differences between HR/HS scans versus HR and all other scan modalities (HR/HS vs. HR/Cube, P = 0.02; HR/HD 5-Line, P = 0.0005; HR/OP, P < 0.0001). CONCLUSIONS: Our data suggest that the reproducibility for SDOCT parameters of DRIL and intraretinal cysts was high across all five SDOCT scan types; thus, evaluation of DRIL is feasible using multiple SDOCT models in eyes with DME. TRANSLATIONAL RELEVANCE: DME morphological changes can be evaluated on multiple SDOCT devices with good reproducibility, allowing clinicians and researchers flexibility in DME assessment for clinical care and research.